SAT0524 THE INCIDENCE RATE OF ADULT ONSET STILL'S DISEASE IN SLOVENIA. (2nd June 2020) - Hocevar, A.; Rotar, Z.; Krosel, M.; Plešivčnik Novljan, M.; Praprotnik, S.; Tomsic, M.
Abstract : Background: Adult Onset Still's disease (AOSD) is an uncommon systemic inflammatory disease. Objectives: To determine for the first time the incidence rate of AOSD in our population. Methods: We retrospectively collected AOSD cases diagnosed between 1 January 2010 and 31 December 2019 at our secondary/tertiary rheumatology centre, which is the only referral centre for an average population of 704, 000 adults. AOSD cases were identified by searching the electronic medical database both for ICD-10 code M06.1 and a full text search for »AOSD«. Patients' records were analyzed and descriptive statistics was used to describe our study group. The adult population was obtained from the national statistics institute database. The annual incidence rate for AOSD was calculated. Results: During the 10-year observation period we identified 22 incipient AOSD cases. All 22 cases fulfilled Yamaguchi classification criteria for AOSD 1 . Five cases were excluded from analyses since they were referred to our department from regions served by other secondary/tertiary centres. Hence, we finally analyzed 17 AOSD cases (11 females; median (IQR) age 38.9 (29.9; 56.5) years, range 20-71 years), resulting in the average annual incidence rate of 2.4 (95%CI 1.5-3.8) cases per 10 6 adults. Age specific incidence rate of AOSD is presented in Figure 1 . Clinical characteristics of AOSD cases at presentation are shown in Table 1 . AOSD was complicated with macrophage activating syndrome in 4/17 (23.5%) cases, and with pulmonary hypertension in one case. Patients were followed for a median (IQR) 31 (20; 58) months. Twelve (70.5%), 2 (11.8%), and 3 (17.6) patients had monophasic, relapsing, and chronic disease course, respectively. Conclusion: AOSD is rare in our population, with an average annual incidence rate of 2.4 cases per 10 6 adults. References: [1]Yamaguchi M, Ohta A, Tsunematsu T, Kasukawa R, Mizushima Y, Kashiwagi H, et al. Preliminary criteria for classification of adult Still's disease. J Rheumatol. 1992;19(3):424-30. Acknowledgments -: Disclosure of Interests: ALOJZIJA HOCEVAR: None declared, Ziga Rotar Consultant of: Speaker and consulting fees from Abbvie, Amgen, Biogen, Eli Lilly, Medis, MSD, Novartis, Pfizer, Roche, Sanofi., Speakers bureau: Speaker and consulting fees from Abbvie, Amgen, Biogen, Eli Lilly, Medis, MSD, Novartis, Pfizer, Roche, Sanofi., Monika Krosel: None declared, Martina Plešivčnik Novljan: None declared, Sonja Praprotnik: None declared, Matija Tomsic: None declared